A speculum. - Ramli, Saiful Hasley (2009)
A speculum (100) having an elongate retractor (101), an annular retaining collar (103), a skirt (102) and an actuator (105) configured to operate the retaining collar (103) between an engaged and disengaged position. The speculum (100) is design to be self retaining once inserted within an animal or human body cavity (400) involving the radial extension of the retaining collar (103) and abutment with the internal walls (404) of the body cavity (400). Examination of the internal cavity walls (404) is possible via exposure through an elongate window (115) formed in the retractor side walls (118).